anonymous
  • anonymous
!!!
Mathematics
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
katieb
  • katieb
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
campbell_st
  • campbell_st
here is a simple method in a quadratic \[y = ax^2 + bx + c\] the line of symmetry is found using \[x = \frac{-b}{2a}\] so in your question a = 3 and b = 6 so find the line of symmetry now the vertex always lies on the line of symmetry, so substitute you answer into the equation to find the value of y.
campbell_st
  • campbell_st
the alternative is to factor out 3 \[y = 3(x^2 + 2x + 1) \] now factor
Pawanyadav
  • Pawanyadav
Coordinates are (-b/2a,-d/4a) b=6 a=3 d=b^2-4ac=6^2-4×3×6=-36 Now put values in coordinates of vertax

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

anonymous
  • anonymous
I did |dw:1434229051281:dw|
anonymous
  • anonymous
Then after I plugged in -1 for x in the equation 3(-1^2)+6(1)+3=6
anonymous
  • anonymous
So the coordinates would be (-1,6) ?
campbell_st
  • campbell_st
well x= -1 is correct... so you substitution has an error \[f(-1) = 3 \times (-1)^2 + 6 \times (-1) + 3 = 0\] so y = 0 and x = -1 then the vertex is (-1, 0) if you factor \[Y = -3(x^2 + 2x + 1) ~~~becomes~~~~y=3(x + 1)^2\] so comparing it to \[y = a(x - h)^2 + k\] h = -1 and k = 0 which is what you go
anonymous
  • anonymous
Oh I see where I made the mistake, I was supposed to do it 3(1)^2. Thank you for your help, again!

Looking for something else?

Not the answer you are looking for? Search for more explanations.